Can robotic technology mitigate the learning curve of total hip arthroplasty?. (1st June 2021) - Kolodychuk, Nicholas; Su, Edwin; Alexiades, Michael M.; Ren, Renee; Ojard, Connor; Waddell, Bradford S.
Abstract : Aims: Traditionally, acetabular component insertion during total hip arthroplasty (THA) is visually assisted in the posterior approach and fluoroscopically assisted in the anterior approach. The present study examined the accuracy of a new surgeon during anterior (NSA) and posterior (NSP) THA using robotic arm-assisted technology compared to two experienced surgeons using traditional methods. Methods: Prospectively collected data was reviewed for 120 patients at two institutions. Data were collected on the first 30 anterior approach and the first 30 posterior approach surgeries performed by a newly graduated arthroplasty surgeon (all using robotic arm-assisted technology) and was compared to standard THA by an experienced anterior (SSA) and posterior surgeon (SSP). Acetabular component inclination, version, and leg length were calculated postoperatively and differences calculated based on postoperative film measurement. Results: Demographic data were similar between groups with the exception of BMI being lower in the NSA group (27.98 vs 25.2; p = 0.005). Operating time and total time in operating room (TTOR) was lower in the SSA (p < 0.001) and TTOR was higher in the NSP group (p = 0.014). Planned versus postoperative leg length discrepancy were similar among both anterior and posterior surgeries (p > 0.104). Planned versus postoperative abduction and anteversion were similar among the NSA and SSA (p > 0.425), whereas planned versus postoperative abduction and anteversion were lower in the NSP (p < 0.001). Outliers > 10 mm from planned leg length were present in one case of the SSP and NSP, with none in the anterior groups. There were no outliers > 10° in anterior or posterior for abduction in all surgeons. The SSP had six outliers > 10° in anteversion while the NSP had none (p = 0.004); the SSA had no outliers for anteversion while the NSA had one (p = 0.500). Conclusion: Robotic arm-assisted technology allowed a newly trained surgeon to produce similarly accurate results and outcomes as experienced surgeons in anterior and posterior hip arthroplasty. Cite this article: Bone Jt Open  2021;2(6):365–370.